COMPOSITIONALITY/NON-COMPOSITIONALITY OF IDIOMS: NON-NATIVE SPEAKERS’ CONSTRAINTS TO COMPREHENSION - Velasco, Yvonne Pedria (Universitas Pendidikan Indonesia, 2016)
Informed by Jackendoff’s (1997) Representational Modularity (RM) Hypothesis which states that, similar to how people make sense of categories, they also systematically make sense of language. This study seeks to discover the way non-native speakers of English negotiate meaning when faced with idiomatic expressions that are modified either by a process of passivization or by a process of quantification; and whether idiom comprehension influence judgments of appropriateness of use of the modified expressions. Employing a researcher-made questionnaire that underwent content validity and reliability tests, the instrument was administered to four college freshman classes from four different higher education institutions. Findings reveal that a significant difference was found between group performance in the passivization and quantification tests through a one-sample test. However, an absence of a statistical relationship between the scores in the test and the participants’ judgment of appropriateness of use (spoken, written, spoken and written) was revealed by the statistical analysis.